STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KAPABILITAS BIROKRASI PUBLIK - Fico Oka Saputra; Banuara Nadeak; Nunung Nurhasanah (JURNAL ILMIAH EDUNOMIKA, 2025)
Human Resources Development (HR) plays a key role in improving the capabilities of the public bureaucracy. Careful evaluation of training programs, understanding the challenges in human resource development, leadership roles, and obstacles in the application of information technology are important in this context. This research aims to explore and analyze HR development strategies in improving public bureaucratic capabilities, as well as to identify related challenges and impacts. This research uses a qualitative approach by conducting direct observations and in-depth interviews with various stakeholders in various public bureaucratic work units. The collected data was analyzed thematically to identify key findings. Evaluation of training programs highlights the need for alignment of training materials with actual employee needs, while challenges in human resource development such as budget constraints and excessive bureaucracy require greater coordinated efforts. The role of leadership is recognized as a key factor in forming an organizational culture that supports human resource development, while obstacles in the application of information technology require special attention. The impact of human resource development includes increasing operational efficiency, quality of public services, and public trust in public bureaucracy. Human resource development is a crucial strategy in increasing the capability of the public bureaucracy. By realizing the existing challenges and taking advantage of the potential positive impacts, sustainable investment and commitment in developing human resources in the public bureaucracy is a must to achieve quality and responsive public services